New membranes obtained by grafted irradiated PVDF foils - Mazzei, R. (2012)
The present work describes a new method to produce membranes of poly(Acrylicacid-Xmonomer) using the grafting procedure. PVDF foils irradiated with Ar+ beamwith energies between 30 and 150 keV were employed as substratum. Differentcombinations of monomers in water solutions were used: acrylic acid (AAc); acrylicacid - glycidyl methacrylate (AAc-GMA); acrylic acid - styrene (AAc-S), acrylic acid-N-isopropyl acrylamide (AAc-NIPAAm) and acrylic acid - N-isopropyl acrylamide -glycidyl methacrylate (AAc-NIPAAm-GMA). A large percentage of grafting results forspecific values of: ion fluence and energy, AAc and sulfuric acid concentration, anddifferent substrata PVDF polymorphous (alpha or beta). At a particular time of thegrafting process, the Poly(AAc-Xmonomer) membranes detach from the substratum andcontinue their grafting in the solution. This method is useful to produce increasedreplicated membranes of the irradiated original surface.